A liquid-crystalline non-fullerene acceptor enabling high-performance organic solar cells - Mondelli, P; Silvestri, F; Ciammaruchi, L; Solano, E; Beltran-Gracia, E; Barrena, E; Riede, M; Morse, G (Royal Society of Chemistry, 2021)
The use of liquid crystalline (LC) compounds in organic photovoltaics has revealed to be an effective strategy to optimise the bulk heterojunction morphology, repairing structural defects through their self-assembling properties. Nonetheless, the design of LC materials has mostly been limited to donor molecules in previous reports. Here we introduce a Non-Fullerene Acceptor (NFA), 4TICO, characterised by an improved structural flexibility, which is imparted by the alkoxy sidechain and favours the formation of LC phases at high temperature. This structural polymorphism also occurs in films where the 4TICO is blended with the PBTZT-stat-BDTT-8 polymer. The high-temperature LC polymorph leads to the formation of a smooth surface morphology with fewer structural defects, providing solar cells with an improved short-circuit current (Jsc) and fill factor (FF), by 14% and 20% respectively. An in-depth investigation of the NFA structural properties in relation to the solar cell performance and charge transport is carried out in comparison to the 4TIC crystalline isomer.